PENGARUH KONSUMSI DAUN KELOR (Moringa oleifera) TERHADAP VO2MAX DAN LACTATE THRESHOLD - Calvin Chandra; Hamidie Ronald Daniel Ray (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2019)
This research aims to determine how the effect of combination of Moringa Leaf consumption with aerobic exercise against VO2Max and Lactate Threshold as ergogenic aids. 16 Taekwondo athletes are participated in this research. Participants are divided into 2 groups: the experimental group, which has been given the treatment of Moringa leaves and aerobic exercise, and the control group, which has been given an aerobic treatment only. The method used is experimental method with randomized pretest-posttest comparison group design. This research took 6 weeks length with aerobic exercise 4 days a week. Moringa leaves consumed at a dose of 2000mg during treatment. The data collection used a Balke Test to measure the VO2max and modified Conconi Test to measure the lactate threshold. The results of this research showed a significant increase in mean before and after treatment in both variables from each group (p <0.05). However, the value of the increase in both variables between the two groups did not show significant difference (p> 0.05). These results, it can be concluded that there is a significant increase of VO2Max and Lactate Threshold between pre test and post test in each group, but there is no significant difference from deviation of increase of between control and experiment group although the experimental group increase is higher than the control group.